LIQUID EFFLUENT TREATMENT IN THE INDUSTRY OF FISH FLOUR - Pizarro C., Raúl (2001)
The study consists on the treatment of pumping water of the fish flour industry, using flotation systems for dissolved air, sedimentation or others as viable methods of primary treatment tor removal of insoluble materials. An the conditioning of a coagulant or flocculant, organic or inorganic, to destabilize the formed micelles to allow the separation of the organic material with the purpose of reaching an effective removal of fine solids in suspension, emulsified fatty and oils and in this way to reduce the biological demand of oxygen of the effluent discharged to the sea.